The impact of India’s farm science centers (Krishi Vigyan Kendras) on farm households’ economic welfare: Evidence from a national farmers survey - Kumar, Anjani; Singh, A. K.; Saroj, Sunil; Madhavan M., Misha; Joshi, Pramod Kumar (International Food Policy Research Institute, 2019)
The paper examines the impact of access to India’s farm science centers (Krishi Vigyan Kendras, or KVKs) on agricultural households’ welfare using household-level data from the nationally representative Situation Assessment Survey of Agricultural Households conducted by India’s National Sample Survey Office in 2013. Employing different matching techniques and endogenous switching regression models, we find that the KVKs have a positive and statistically significant impact on agricultural households’ economic welfare, although that impact is heterogeneous. Further, the investments made in expansion of India’s network of KVKs have been quite remunerative, as the benefit-to-cost ratio of expenditure on KVKs ranges from 8 to 12. Moreover, our findings suggest that expanding rural formal credit markets and promoting literacy can maximize the potential impact of KVKs on agricultural households’ economic welfare.